2015
DOI: 10.14302/issn.2324-7339.jcrhap-15-648
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perception And Practice Of Preventive Lifestyle Against HIV/AIDS Among Students Of A Tertiary Educational Institution In South Eastern Nigeria.

Abstract: HIV/AIDS has become a global scourge affecting mainly young people. Sexual behavior change remains the most effective way of preventing further spread. The aim of this study is to assess the knowledge, perception and practice of safe lifestyles towards prevention of HIV infection among students of a tertiary educational institution in Abakaliki, south eastern, Nigeria. A cross sectional descriptive study was carried out, and participants were selected using multistage sampling technique. Data was collected usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…This means that students have information about the prevention of HIV/AIDS, but it needs strengthening. This finding is somewhat congruent with that of the study by Ngozi et al (2015) which revealed that preventive measures on HIV /AIDS are practiced by the respondents. However, the authors added that their respondents felt threatened in using preventive measures.…”
Section: Knowledge On Hiv/aids Of Students-respondents As Tosupporting
confidence: 89%
“…This means that students have information about the prevention of HIV/AIDS, but it needs strengthening. This finding is somewhat congruent with that of the study by Ngozi et al (2015) which revealed that preventive measures on HIV /AIDS are practiced by the respondents. However, the authors added that their respondents felt threatened in using preventive measures.…”
Section: Knowledge On Hiv/aids Of Students-respondents As Tosupporting
confidence: 89%
“…The range of scores was between 4 and 18, with 2(1.1%) having the lowest score of 4, while only 1 student had a maximum score of 18. The median (IQR) score was 13 (12)(13). Similarly, a composite score was calculated to determine the level of appropriate preventive practices in the students with a minimum score of 0 and a maximum of 8.…”
Section: Practice Of Hiv and Sti Prevention Among The Studentsmentioning
confidence: 99%
“…A lot of gap still exist between knowledge and sexual practices among different groups of people or populations. [10] Though knowledge of STIs appears to be generally high among many students in Nigeria, [11][12][13] it was recently shown to be poor among secondary school students in Ado Ekiti, South West Nigeria. [14] The gap is as a result of ambiguous information [15] , resulting in discordance between high knowledge and risky sexual behaviours which was not only demonstrated in many studies from all over Nigeria, [11][12][13] but also beyond Nigeria such as among medical students of a Caribbean university and high school students in Lao PDR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation